2020
DOI: 10.1590/0034-7167-2018-0793
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the discontinuance of outpatient follow-up in neonatal units

Abstract: Objectives: to identify predisposing and enabling factors as well as the health needs associated with the discontinuance of outpatient follow-up of newborns who were hospitalized at neonatal intensive care unit. Methods: cross-sectional study, using the behavioral model of health services use. The study was composed of 358 mothers and newborns referred to the outpatient follow-up after discharge. Characterization, perception of social support, postnatal depression, and attendance to appointments data were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
0
6
0
2
Order By: Relevance
“…Cabendo aos familiares traçarem seu itinerário em busca de suporte. Estudo mostrou que o apoio informacional nas UTIN e no seguimento após a alta ainda apresenta lacunas, comprometendo a potencialização do cuidado parental e a compreensão das famílias sobre a condição de saúde e necessidades da criança pré-termo 10 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Cabendo aos familiares traçarem seu itinerário em busca de suporte. Estudo mostrou que o apoio informacional nas UTIN e no seguimento após a alta ainda apresenta lacunas, comprometendo a potencialização do cuidado parental e a compreensão das famílias sobre a condição de saúde e necessidades da criança pré-termo 10 .…”
Section: Discussionunclassified
“…As famílias de RNPT egressos de UTIN vivenciam falhas nas orientações recebidas no preparo para a alta, desarticulação entre os serviços em que a criança é atendida, falta de apoio familiar e social, dificuldades de acesso aos serviços no que diz respeito à distância do domicílio até as unidades de saúde e o tempo despendido com esse deslocamento, e dificuldade de agendamento para os atendimentos 4/15 necessários, evidenciando fragilidades na continuidade do cuidado 9 . Ademais, a dependência de tecnologias por estas crianças e o desconhecimento por parte dos profissionais de fatores de risco para o não seguimento estão associados à descontinuidade do acompanhamento ambulatorial 10 .…”
Section: /15 Introduçãounclassified
“…These reflexes portray and corroborate the findings of this study as the (i)responsibility for the concrete transfer of premature infants reflects in their first absent access. The lack of scientific and technical knowledge, specific about the growth and development of premature births, implies in many cases, the lack of trust of parents to maintain the bond in the service (26)(27) . The team of preterm follow-up clinics linked to these children's birth hospitals could optimize referral and counter-referral with the care network, stimulating the bond, a fact that was not demonstrated in the statements.…”
Section: Discussionmentioning
confidence: 99%
“…Studies corroborate the description of the network found in this study for premature births as less than half of premature infants remain in RAS. The main problems of lack of adherence are the lack of immunization, the absence of preventive care guidance for age and the fragile bond with PHC professionals for follow-up and timid referral and counter-referral (26)(27)(28) . It is understood that PHC should be the point of attention in the health system that offers entry to that system for needs and problems, providing care for people and their families over time and in all conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation